Sulfur Analogs of the Core Formose Cycle: A Free Energy Map - Jeremy Kua; Maria T. Peña; Samantha N. Cotter; John Leca (Life)
Using computational methods, we examine if the presence of H2S can tame the unruly formose reaction by generating a free energy map of the reaction thermodynamics and kinetics of sulfur analogs within the core cycle. With mercaptoaldehyde as the linchpin C2 species, and feeding the cycle with CH2O, selected aldol additions and enolizations are kinetically more favorable. Thione formation is thermodynamically less favored compared to aldehydes and ketones, but all these species can be connected by enolization reactions. In some sulfur analogs, the retroaldol transformation of a C4 species back into linchpin species is thermodynamically favorable, and we have found one route incorporating where incorporating sulfur selects for a specific pathway over others. However, as CH2O diminishes, the aldol addition of larger species is less favorable for the sulfur analogs. Our results also suggest that competing Cannizzaro side reactions are kinetically less favored and thermodynamically disfavored when H2S is abundant.